Banks and sovereign risk: evidence from earnings announcements - Braga, Otávio Luiz Mattarello (2020)
A growing literature highlights the relation between bank crises and sovereign defaults. However, causal estimates of the effect of banks on sovereign risk, under plausible identifying assumptions, are badly missing from this literature. This paper attempts to fill this gap by exploring the exogenous shocks to bank equity provided by bank earnings announcements. Since the surprise in earnings announcements is not observable, we employ the method of identification through heteroskedasticity. Using data from Brazil, we find that a 10% fall in bank equity leads to an increase in default risk of around 1-3 percentage points. We do not see any significant effect when we replace the banking sector by the retail industry, state companies, or the stock market as a whole. Hence, banks seem to be indeed particularly relevant drivers of sovereign risk.